2014
DOI: 10.1364/oe.22.029805
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional super-resolution structured illumination microscopy with maximum a posteriori probability image estimation

Abstract: We introduce and demonstrate a new high performance image reconstruction method for super-resolution structured illumination microscopy based on maximum a posteriori probability estimation (MAP-SIM). Imaging performance is demonstrated on a variety of fluorescent samples of different thickness, labeling density and noise levels. The method provides good suppression of out of focus light, improves spatial resolution, and allows reconstruction of both 2D and 3D images of cells even in the case of weak signals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…Our method includes detailed information about the shape of the PSF of the imaging system. Information about the shape of the PSF can be important for PSF fitting photometry in astronomy [47], for deconvolution algorithms in microscopy [48,49] and for other applications. Our model of the UWFOV system was successfully used by Fliegel [50] for a comparison of the deconvolution methods.…”
Section: Experimental Laboratory Resultsmentioning
confidence: 99%
“…Our method includes detailed information about the shape of the PSF of the imaging system. Information about the shape of the PSF can be important for PSF fitting photometry in astronomy [47], for deconvolution algorithms in microscopy [48,49] and for other applications. Our model of the UWFOV system was successfully used by Fliegel [50] for a comparison of the deconvolution methods.…”
Section: Experimental Laboratory Resultsmentioning
confidence: 99%
“…Briefly, the SIM system uses a ferroelectric liquid crystal on silicon (LCOS) microdisplay (type SXGA-3DM, Forth Dimension Displays). This device has been used previously in SIM and related methods in fluorescence microscopy [5,10,15,33,[43][44][45][46][47] and allows one to produce patterns of illumination on the sample which can be reconfigured at will by changing the image displayed on the device. The light source (Lumencor Spectra-X) is toggled off between SIM patterns and during camera readout.…”
Section: Microscope Setup and Data Acquisitionmentioning
confidence: 99%
“…SIM reconstructions were performed using SIMToolbox, an open-source and freely available program that our group developed for processing SIM data [33]. We generated optically sectioned, enhanced resolution images using a Bayesian estimation method, maximum a posteriori probability SIM (MAP-SIM) [15]. MAP-SIM works using maximum a posteriori probability methods, which are well known in microscopy applications [48,49], to enhance high spatial frequency image information.…”
Section: Sim Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to new illumination schemes, alternative data processing methods have also been introduced [27][28][29][30][31][32][33]. For example, Orieux et al suggested a 2D method for SIM reconstruction based on Bayesian estimation [28], and our group showed that Bayesian reconstruction methods in SIM have several potential advantages and can achieve a performance comparable to traditional SIM methods [29].…”
mentioning
confidence: 99%